The summer girl eaudiobook - Kennedy, Elle (Avalon Bay, 2023)
Elle Kennedy's next spicy and emotional romance in the blockbuster Avalon Bay series. College student Cassie Soul hasn't spent an entire summer in Avalon Bay in years, not since her parents divorced and her mother spitefully whisked her away to Boston. Now that her grandmother is selling the boardwalk hotel that's been in their family for five decades, Cassie returns to the quaint beach town to spend time with family, ring in her twenty-first birthday...and maybe find herself a summer fling. On her first night in town, she finds the perfect candidate: Tate Bartlett, Avalon Bay's fun-loving golden boy. Tate, sailing instructor and lovable player, is no stranger to flings. In fact, he's always down for a good time. But the moment he meets Cassie, he knows she's not the girl you play games with. Cassie is gorgeous, hilarious, and, frankly, the coolest person he's ever met. The last thing he wants to do is risk breaking her heart, and so he reluctantly puts her in the friend-zone...only to realize he made a huge mistake. Soon, his attraction to Cassie becomes impossible to ignore. He wants that fling now. Big-time. And maybe even something more. As Cassie and Tate walk the line between friends and lovers, they're about to discover that their situation is the least complicated part of this equation. Because Avalon Bay is full of secrets—and their relationship might not survive when those secrets come to light. A Macmillan Audio production from St. Martin's Press.